2012
DOI: 10.1002/jssc.201200062
|View full text |Cite
|
Sign up to set email alerts
|

Development of magnetic multiwalled carbon nanotubes as solid‐phase extraction technique for the determination of p‐hydroxybenzoates in beverage

Abstract: In this work, magnetic multiwalled carbon nanotubes were synthesized through a facile hydrothermal process, and then successfully used as magnetic solid-phase extraction sorbents for the determination of p-hydroxybenzoates in beverage. The prepared magnetic multiwalled carbon nanotubes presented both satisfactory superparamagnetism and strong capacity of absorption, with magnetic Fe(3)O(4) beads of 200 nm average diameters decorated at either ends of the tubes. The hybrid nanocomposites showed a high efficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…In 2010, Morales-Cid et al [45] reported PAHs have been preconcentrated from several food samples, such as edible oils [90] and grilled meat [58], using magnetic-MWCNTs prepared by co-precipitation of iron salts and subsequent magnetite particle aggregation on the nanotube surface as the sorption material. In both cases, detection was carried out by gas chromatography mass spectrometry (GC-MS) and good LODs (0.10-0.88 and 0.035-010 ng g -1 , respectively) and acceptable inter-and intra-day precision (<9% and <13.9%) were achieved bearing Other applications of M-SPE with strategies similar to those described above have been reported for the determination of other organic compounds in environmental and food samples, including para-hydroxybenzoates [61], linear alkylbenzene sulfonates [105] (from C 10 to C 13 ) and 4-nonylphenol [106] (See Table 3 for details). can be seen from the data in Table 3 that this strategy represents the best approach to achieve the fast analysis of numerous analytes per sample with good precision and accuracy and with excellent sensitivity.…”
Section: Organic Compoundsmentioning
confidence: 86%
See 2 more Smart Citations
“…In 2010, Morales-Cid et al [45] reported PAHs have been preconcentrated from several food samples, such as edible oils [90] and grilled meat [58], using magnetic-MWCNTs prepared by co-precipitation of iron salts and subsequent magnetite particle aggregation on the nanotube surface as the sorption material. In both cases, detection was carried out by gas chromatography mass spectrometry (GC-MS) and good LODs (0.10-0.88 and 0.035-010 ng g -1 , respectively) and acceptable inter-and intra-day precision (<9% and <13.9%) were achieved bearing Other applications of M-SPE with strategies similar to those described above have been reported for the determination of other organic compounds in environmental and food samples, including para-hydroxybenzoates [61], linear alkylbenzene sulfonates [105] (from C 10 to C 13 ) and 4-nonylphenol [106] (See Table 3 for details). can be seen from the data in Table 3 that this strategy represents the best approach to achieve the fast analysis of numerous analytes per sample with good precision and accuracy and with excellent sensitivity.…”
Section: Organic Compoundsmentioning
confidence: 86%
“…Scanning electron microscopy Morphological analysis, aggregation state [116] Transmission electron microscopy Morphological analysis of internal structure, aggregation state [46] X-ray diffraction Morphological analysis of bulk samples [55] Spectroscopic techniques Raman spectroscopy Purity, diameter distribution, functionalization [40] Infrared spectroscopy and Fourier transform infrared spectroscopy Functionalization by attaching functional groups to the sidewall [52] X-ray photoelectron spectroscopy and Energy dispersive spectroscopy Elemental composition, functionalization by attaching functional groups to the sidewall [54] Thermal techniques Thermogravimetric analysis Purity and presence of by-products, quality control of synthesis and manufacture processes [47] Magnetic techniques Vibrating sample magnetometry Magnetic properties [53] Alternating gradient magnetometry Magnetic properties [46] Superconducting quantum interference device Magnetic properties [61] M A N U S C R I P T…”
Section: Microscopy and Diffraction Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the dispersion extraction mode can increase the overall extraction efficiency , and most magnetic adsorbents can be recycled and reused . The advantages of the rapidity, simplicity, and reduced cost, labor, and time render MSPE a prospective method for sample preparation .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the efficient contact area between the sorbents and analytes increases largely due to the dispersive extraction mode, and the majority of magnetic sorbents can be recycled and reused easily . Therefore, MSPE has comprehensive advantages for simplifying the process and saving time and labor, which indicates its bright application prospect for sample preparation .…”
Section: Introductionmentioning
confidence: 99%